2019
DOI: 10.3390/app9153051
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Amphiphilic Chitosan–Graphene Oxide–Cellulose Nanocrystalline Composite Hydrogels and Their Biocompatibility and Antibacterial Properties

Abstract: Environmental-friendly nanocomposite hydrogels of carboxymethyl-hexanoyl chitosan (CHC), graphene oxide (GO) and cellulose nanocrystals (CNCs) were combined to produce a bio-hydrogel with great biocompatibility and antibacterial ability. The size of the GO nanosheets was about 200–500 nm, and the CNCs had a length of 100–200 nm and a width of 10–20 nm, as shown by transmission electron microscopy (TEM). X-ray photoelectron spectroscopy (XPS) was utilized for the analysis of the oxygen functional groups of GO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Recent studies have shown that the synergistic effect between CS and GO generates hybrids with not only improved thermal stability, mechanical and optical properties ( Chen et al., 2019 ; Cobos et al., 2017 ; Kumar and Koh, 2014 ; Zhang et al., 2018a ) but also excellent in vitro and in vivo biocompatibility ( López Tenorio et al., 2019 ; Valencia et al., 2021 ; Zhang et al., 2021 ), angiogenic and cell growth effect ( Zhang et al., 2018b , 2021 ), antimicrobial properties ( Grande et al., 2017 ; Khalil et al., 2020 ), electrical conductivity ( Jiang et al., 2019 ) and adsorption capacities ( Wu et al., 2020a ; Yu et al., 2017b ), etc. Therefore, nanocomposites containing CS and GO have been widely created for developing improved thermomechanical and antimicrobial properties of food packaging film ( Ahmed et al., 2017 ; Grande et al., 2017 ), conductive three-dimensional scaffolds, coating, and nanofiber for tissue engineering ( Arnaldi et al., 2020 ; Cao et al., 2017 ; Jiang et al., 2019 ; Karimi et al., 2019 ), nanoparticle and hydrogel with great loading capacity and releasing profile for drug delivery ( Wang et al., 2018a ; Zhao et al., 2017b ), antibacterial film and hydrogel patch for wound healing ( Najafabadi et al., 2020 ; Yang et al., 2019c ), nanofiber and film with high load carrying capacity and electrochemical properties for biosensor ( Fazial and Tan, 2021 ; Li et al., 2019 ), sponge and membrane with strong adsorption power for wastewater treatment ( Bandara et al., 2019 ; Qi et al., 2018 ), and so on . In view of the broad uses of CS–GO nanocomposites in the past few years and the bright future, it is meaningful to summarize the latest advances convenient for further study and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the synergistic effect between CS and GO generates hybrids with not only improved thermal stability, mechanical and optical properties ( Chen et al., 2019 ; Cobos et al., 2017 ; Kumar and Koh, 2014 ; Zhang et al., 2018a ) but also excellent in vitro and in vivo biocompatibility ( López Tenorio et al., 2019 ; Valencia et al., 2021 ; Zhang et al., 2021 ), angiogenic and cell growth effect ( Zhang et al., 2018b , 2021 ), antimicrobial properties ( Grande et al., 2017 ; Khalil et al., 2020 ), electrical conductivity ( Jiang et al., 2019 ) and adsorption capacities ( Wu et al., 2020a ; Yu et al., 2017b ), etc. Therefore, nanocomposites containing CS and GO have been widely created for developing improved thermomechanical and antimicrobial properties of food packaging film ( Ahmed et al., 2017 ; Grande et al., 2017 ), conductive three-dimensional scaffolds, coating, and nanofiber for tissue engineering ( Arnaldi et al., 2020 ; Cao et al., 2017 ; Jiang et al., 2019 ; Karimi et al., 2019 ), nanoparticle and hydrogel with great loading capacity and releasing profile for drug delivery ( Wang et al., 2018a ; Zhao et al., 2017b ), antibacterial film and hydrogel patch for wound healing ( Najafabadi et al., 2020 ; Yang et al., 2019c ), nanofiber and film with high load carrying capacity and electrochemical properties for biosensor ( Fazial and Tan, 2021 ; Li et al., 2019 ), sponge and membrane with strong adsorption power for wastewater treatment ( Bandara et al., 2019 ; Qi et al., 2018 ), and so on . In view of the broad uses of CS–GO nanocomposites in the past few years and the bright future, it is meaningful to summarize the latest advances convenient for further study and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GO modification with organic compounds that possess the antimicrobial activity and biocompatibility have been intensively studied very recently, e.g., chitosan (CS) [92,[101][102][103], curcumin [104,105], antimicrobial agents (isoniazid (INH), amikacin (AMK) and linezolid (LZD), lincomycin hydrochloride (LMH), chloramphenicol (CPC) and gentamycin sulfate (GMS) [106,107]) and dyes [108]. Chitosan exhibits high biocompatibility, biodegradability and antibacterial properties [109].…”
Section: Antimicrobial Properties Of Graphene-based Composite Photocatalystsmentioning
confidence: 99%
“…The simultaneous incorporation of CNC and GO to numerous polymers such poly(3-hydroxybutyrate-co-3-hydroxy valerate) [ 164 ], poly-N-isopropyl acrylamide [ 165 ], poly(3,4-ethylenedioxythiophene) [ 166 ], poly(vinylidene fluoride) [ 167 ], polyacrylamide [ 168 ], poly(ε-caprolactone) [ 169 ], polylactic acid [ 170 ], poly(vinyl alcohol) (PVA) [ 171 ] and chitosan [ 172 ] was adopted as an efficient method to produce composites with excellent features since these nanofillers offer outstanding synergetic effects. Some surface modifications can be applied to CNC or GO to improve their dispersion and compatibility within the polymeric matrices.…”
Section: Preparation Properties and Application Of Cnc/gnm Hybridmentioning
confidence: 99%
“…Some surface modifications can be applied to CNC or GO to improve their dispersion and compatibility within the polymeric matrices. This type of nanocomposite found a wide range of applications in biosensing [ 165 ], plastic masks [ 172 ], tissue engineering [ 168 , 169 ], wastewater treatment [ 167 ], food packaging [ 173 ], supercapacitors [ 166 ], to cite a few. For instance, El Miri et al evaluated the synergetic effect of CNC/GO as a functional hybrid to enhance the properties of PVA nanocomposites ( Figure 11 I).…”
Section: Preparation Properties and Application Of Cnc/gnm Hybridmentioning
confidence: 99%